Efeitos dos tratamentos superficiais dos resíduos industriais de fibra de piaçava nas propriedades térmicas e termodinâmico-mecânica de compósitos à base de Polihidroxibutirato (PHB) - Santos, Eduardo Braga Costa (2019)
The aim of this work was prepare and characterize polyhydroxybutyrate (PHB) reinforced by leftover fibers from the broom industry. The fibers were sorted, cut, washed in a 2%-detergent solution, milled in a knife mill and stirred for later surface treatment with sodium hydroxide (NaOH), calcium hydroxide (Ca(OH)2) solutions and heat treatment with distilled water at 75 ºC. These same fibers were also treated with coupling agent to compare their thermal properties with each other and with that of the in natura fiber reinforced composite. The following characterizations were made: X-Ray Diffraction (XRD), optical (OM) and scanning electron microscopy (SEM), thermogravimetry analysis (ATG), particle size distribution, moisture rate (ASTM D1384), surface area (BET) and Dynamic-ThermalMechanical Analysis (DMA) and Fourier Transform Infrared (FTIR) Spectroscopy tests were performed. The surface of the Ca(OH)2 treated fiber showed calcium carbonate crystals under the fiber surface, which were formed due to the insolubility of this alkali during the time of the experiment. The other treatments positively modified the "in natura" surface fiber, increasing its surface area, decreasing its diameter and its surface became more clear, however its moisture absorption rate was increased. Furthermore, the surface treatments had not modified the piassava fiber’s crystalline structure. However, the alkalis were inefficient for the treatment of fiber to be used in the development of PHB-reinforced composites, since processing was impossible to NaOH-treated fiber composite. In addition, the Ca(OH)2 treated fiber composites presented the lowest degradation temperature in and lowest activation energy than the other samples according the Kissinger Kinetic Model, observing the other samples due to the influence of fiber mineralization process. The 75 ºC hot-water fiber surface treatment, further to be an ecological and economically cheap method, it showed favorable for the composite manufacturing, increasing its activation energy (Ea). The silane treated fiber composites showed higher Ea values than other composites, as well as a higher storage modulus value and lower loss factor, suggesting that interfacial adhesion occurred in this composite.